Estimating bloodstain formation time by quantitative analysis of mtDNA degradation. (October 2022) - He, Hongxia; Zhang, Qingxia; Niu, Qing; Li, Yeming; Sun, Qifan; Zhao, Dong
Abstract: The estimation of bloodstain formation time is still an unsolved problem in forensic science and lacks accurate quantitative methods. Whether DNA can be adopted to estimate bloodstain formation time is still controversial, and there is no study to confirm the potential of mtDNA markers. To address these issues, a triple quantification method based on the ratio of mtDNA fragments of different lengths of COⅠ (mitochondrially encoded cytochrome c oxidase Ⅰ) for estimating bloodstain formation time was established. A total of 152 samples (140 old samples, 12 fresh samples) were collected and tested, and the absolute copies of different-sized fragments of COⅠ (304 bp, 120 bp, 41 bp) in all samples were quantified by SYBR Green real-time qPCR. The natural logarithms of two copy number ratios (304 bp/41 bp, 120 bp/41 bp) of COⅠ in old samples were calculated, which were used as degradation indexes to evaluate the degradation degree of mtDNA. The 140 old human blood samples from 1 to 14 years of storage were accumulated from casework of forensic practice to establish the method of estimating bloodstain formation time and used to analyze the impact of gender factors on the two degradation indexes, and 10 animal samples and 2 fresh human samples were collected to verify the human specificity of the method. There was a high correlation between degradation indexes and bloodstain formation time (the absolute values of correlation coefficients of these two degradation indexes were 0.901 and 0.758 respectively). A method with triple quantification and dual indexes estimating bloodstain formation time was successfully established, which was highly human-specific. There was no statistically significant difference in degradation indexes between different gender samples (P > 0.05). This study confirmed that mtDNA can be utilized to estimate bloodstain formation time, which provides a new solution to the forensic problem of estimating the time of bloodstain formation. Highlights: It's the first time to verify the feasibility of mtDNA quantitative analysis in estimating bloodstain formation time. It's the first time that a triple quantification method was successfully established to estimate bloodstain formation time using DNA. It's the first time to use COⅠ with high human specificity to estimate bloodstain formation time.